The Influence of Service Quality in Increasing Competitiveness and Consumer Satisfaction - Suryadi Amin; Dian A.S Parawansa; Andi Aswan (Magister Management, Hasanuddin University, 2021)
The purpose of this study is to analyze the effect of service quality on customer satisfaction using competitiveness as a mediating variable at Depo Petikemas, a unit business of PT. Industrial Estate of Makassar (Persero). This study uses a quantitative approach with path analysis. The data was obtained by distributing questionnaires to 60 respondents from 30 enterprise consumers. The results of the study indicate that when the company provides quality services, the company’s competitiveness will be stronger as the company ensures customer satisfaction to those who use services at the Petikemas Depo at PT. Industrial Estate of Makassar (Persero).